2021
DOI: 10.1136/bmjsem-2021-001157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a cervical collar on head and neck acceleration profiles during emergency spinal immobilisation and extrication procedures in elite football (soccer) players: protocol for a randomised, controlled cross-over trial

Abstract: When immobilisation after a cervical spine or head injury is required, the role of the rigid cervical collar is unclear and controversial. There is a need for further studies investigating the use of a rigid cervical collar when head and neck trauma occurs in sport. This study will compare present practice (immobilisation with a cervical collar) to the same procedure without a collar during a simulated spinal immobilisation and extraction scenario from the field of play to the side-line in football (soccer). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Each procedure was performed three times with and three times without the collar without removing the IMUs. The equipment used is fully described in the protocol 21 and included the Laerdal Stifneck Select Cervical collar (Laerdal Medical, Stavanger, Norway).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each procedure was performed three times with and three times without the collar without removing the IMUs. The equipment used is fully described in the protocol 21 and included the Laerdal Stifneck Select Cervical collar (Laerdal Medical, Stavanger, Norway).…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted and reported according to the recommendations of the Consolidated Standards of Reporting Trials (CONSORT) statement extension for within person randomised trials 20 . A detailed protocol of the RESTRICT study has been published elsewhere 21 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation